Effects of water addition level on physical properties, rheological profile and sensory evaluation of gluten-free bread : a preliminary approach - Norashikin Mohd Zain,; Maaruf Abd. Ghani,; Zalifah Mohd Kasim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The amount of water in gluten-free recipes is very important to the quality of the end product. The research aimed to develop an alternative formula for gluten-free bread using different water levels. This research was conducted to determine the physical properties, rheological profile and sensory evaluation of natural gluten-free bread produced by adding different water levels to the recipe without adding hydrocolloid. Five types of bread with different levels of water at (A) 80%; (B) 90%; (C) 100%; (D) and control dough: 105% (control 1); (E) 60% (wheat breadcontrol 2) of the flour basis were investigated. Control 1 is the standard level of water for making gluten-free bread, while control 2 is the standard level of water for preparing wheat bread. Sample A has a lighter crust and crumbs, as well as a white index value and lower ΔE values comparable to wheat bread, better volume, increased pore size sharply and shows higher G’ and G”. G’ decreased as the amount of water in the dough increased. All dough formulations had higher gelatinisation enthalpy change (ΔH) values than sample A and sample E. The bakery sector could use the findings to design and reformulate the recipes of diabetic and/or reduced calorie and gluten-free bread recipes to better fulfill consumers’ expectations.